The enemy of my friend is my enemy: Chinese leaders' foreign visits and transnational repression of Uyghurs - Oztig, Lacin Idil; Karluk, Abdurresit Celil (SAGE PUBLICATIONS INC, 2025)
China has been targeting Uyghurs indiscriminately in many countries around the world. However, the Uyghur diasporas in some countries are more susceptible to China's repressive practices than in other countries. What explains cross-country variations regarding China's repression of Uyghurs abroad? In this study, we explain this variation by laying out a causal linkage between Chinese leaders' foreign visits and transnational repression of Uyghurs. We argue that China's rising global power translates into political weight over countries it frequently interacts with. For such countries, maintaining the status quo in bilateral relations is advantageous, whereas alienating China is costly. This dynamic highlights the importance of complying with China's strategic interests, one of which is the repression of the Uyghur diasporas around the world. As such, we expect countries that host the Uyghur population and witness the visits of Chinese leaders to operate according to the logic the enemy of my friend is my enemy and allow and even help China's (the friend's) repressive activities against Uyghurs (the enemy of my friend) on their soil. Drawing on the Transnational Repression of Uyghurs Dataset and examining 43 countries in the period 1998-2020, we find a positive and statistically significant relationship between Chinese leaders' foreign visits and transnational repression of Uyghurs: the more a Chinese leader visits a country, the more likely it is that diaspora Uyghurs are subject to Chinese repression. We also find a positive relationship between Chinese leaders' foreign visits and the severity of China's transnational repression.
Keywords: China; diaspora; leader visits; transnational repression; Uyghurs; INTERNATIONAL HUMAN-RIGHTS; REGRESSION; COOPERATION; DIPLOMACY; POLICY; BELT; ROAD; International Relations